Intermitências da vida: o professor o aluno e a morte na centralidade das aprendizagens na graduação em enfermagem - Pinheiro, Monalisa da Silva (Universidade do Vale do Rio dos Sinos, 2013)
This study aims to understand how nursing undergraduate professors and students interact during knowledge production related to the palliative care of patients with terminal conditions. Our main main objectives were the following: (1) Understand how the processes of teaching / learning that focus on theoretical-practical activities produce knowledge along patient care on the health services; (2) Know the learning strategies used by undergraduate nursing professors, or the lack thereof, in teaching with patients on terminal process; (3) Identify how professors act in regard to the complex learning experiences of their students; (4) Contribute to the field of teaching in higher education programs. A qualitative research method was used, which included performing semi-structured interviews with six professors of a nursing college, who all act as learning supervisors for more than 5 years, as well as the students of the same course. The collected data was organized in three dimensions: (1) Among work and the university: the origins of knowledge of female nursing professors; (2) Pedagogic strategies for relationships between students, professors and patients in terminal process; (3) Challenges in everyday teaching at the bedside. The literature revision and our findings from the interviews help to understand that approaching the subject of “palliative care” is a complex and multifaceted activity. Learning to perform care of patients suffering from terminal conditions seems to be possible only with a reflection of human existence and the understanding of the inevitable ending of human life. As soon as we consider death as part of life, we will be able to approach this subject openly, diminishing the suffering of all those involved in the process. This study demonstrates that many educational programs don’t explicitly include this subject on the undergraduate schools curriculum, leaving it the discretion of professors in real situations. At the same time, it demonstrates the importance of formal training in palliative care for nursing professionals.
Keywords: Saberes docentes; Enfermagem; Morte; Educação superior; Teacher knowledges; Nursing; Death; Under-gratuate education; ACCNPQ::Ciências Humanas::Educação